2020
DOI: 10.1002/ijgo.13335
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of the COVID‐19 pandemic among pregnant women in Sri Lanka

Abstract: The COVID‐19 pandemic has caused increased rates of perinatal anxiety and depression in pregnant women with no known COVID‐19 infection in Sri Lanka.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 7 publications
5
86
3
3
Order By: Relevance
“…A total of 23 studies (Ayaz et al, 2020;Berthelot et al, 2020;Ceulemans et al, 2020;Durankuş and Aksu, 2020;Farewell et al, 2020;Gu et al, 2020;He et al, 2020;Lebel et al, 2020;Li et al, 2020;Liu et al, 2020;Mappa et al, 2020;Matsushima and Horiguchi, 2020;Oskovi-Kaplan et al, 2020;Parra-Saavedra et al, 2020;Patabendige et al, 2020;Preis et al, 2020;Saccone et al, 2020;Sade et al, 2020;Silverman et al, 2020;Wu et al, 2020b;Yue et al, 2020;Zanardo et al, 2020;Zhang and Ma, 2020) performed with 20 569 participants (16,797 pregnant women and 3,772 postpartum women) during the COVID-19 pandemic and with 3,677 pregnant women before the COVID-19 pandemic were included in this systematic review and metaanalysis. A total of 19 studies (Ceulemans et al, 2020;Durankuş and Aksu, 2020;Farewell et al, 2020;He et al, 2020;Lebel et al, 2020;Li et al, 2020;Liu et al, 2020;Mappa et al, 2020;Matsushima and Horiguchi, 2020;Oskovi-Kaplan et al, 2020;Parra-Saavedra et al, 2020;Patabendige et al, 2020;Preis et al, 2020;Saccone et al, 2020;…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 23 studies (Ayaz et al, 2020;Berthelot et al, 2020;Ceulemans et al, 2020;Durankuş and Aksu, 2020;Farewell et al, 2020;Gu et al, 2020;He et al, 2020;Lebel et al, 2020;Li et al, 2020;Liu et al, 2020;Mappa et al, 2020;Matsushima and Horiguchi, 2020;Oskovi-Kaplan et al, 2020;Parra-Saavedra et al, 2020;Patabendige et al, 2020;Preis et al, 2020;Saccone et al, 2020;Sade et al, 2020;Silverman et al, 2020;Wu et al, 2020b;Yue et al, 2020;Zanardo et al, 2020;Zhang and Ma, 2020) performed with 20 569 participants (16,797 pregnant women and 3,772 postpartum women) during the COVID-19 pandemic and with 3,677 pregnant women before the COVID-19 pandemic were included in this systematic review and metaanalysis. A total of 19 studies (Ceulemans et al, 2020;Durankuş and Aksu, 2020;Farewell et al, 2020;He et al, 2020;Lebel et al, 2020;Li et al, 2020;Liu et al, 2020;Mappa et al, 2020;Matsushima and Horiguchi, 2020;Oskovi-Kaplan et al, 2020;Parra-Saavedra et al, 2020;Patabendige et al, 2020;Preis et al, 2020;Saccone et al, 2020;…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…A total of 19 studies (Ceulemans et al, 2020;Durankuş and Aksu, 2020;Farewell et al, 2020;He et al, 2020;Lebel et al, 2020;Li et al, 2020;Liu et al, 2020;Mappa et al, 2020;Matsushima and Horiguchi, 2020;Oskovi-Kaplan et al, 2020;Parra-Saavedra et al, 2020;Patabendige et al, 2020;Preis et al, 2020;Saccone et al, 2020;Sade et al, 2020;Silverman et al, 2020;Wu et al, 2020b;Yue et al, 2020;Zhang and Ma, 2020) were cross-sectional, and 4 (Ayaz et al, 2020;Berthelot et al, 2020;Gu et al, 2020;Zanardo et al, 2020) were case-control studies. Among the 23 studies, 7 were located in China (Gu et al, 2020;He et al, 2020;Li et al, 2020;Liu et al, 2020;Wu et al, 2020b;Yue et al, 2020;Zhang and Ma, 2020), 3 were implemented in America (Farewell et al, 2020;Preis et al, 2020;Silverman et al, 2020), 3 were performed in Turkey (Ayaz et al, 2020;Durankuş and Aksu, 2020;Oskovi-Kaplan et al, 2020), 3 were undertaken in Italy (Mappa et al, 2020;Saccone et al, 2020;…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies published in the last months on the effect of the Covid-19 pandemic on pregnancy and childbirth have mainly focused on medical conditions and risk factors and have attempted to pinpoint the measures and clinical recommendations required to contain the Covid-19 spread (e.g., Chen et al, 2020;Liang and Acharya, 2020). The scant literature that has addressed the psychological impact of the Covid-19 pandemic on expectant and postpartum women has found higher levels of anxiety and depressive symptoms among participants when compared to similar cohorts assessed before the outbreak (Ceulemans et al, 2020;Lebel et al, 2020;Liu et al, 2020;Patabendige et al, 2020). An Italian study investigating the psychological effects of the pandemic on pregnant women found a significant change in their expectations toward pregnancy and childbirth as well as an increase in their concerns and distress, especially if they had a previous history of psychological distress in press (Ravaldi et al, 2020).…”
Section: Psychological Well-being During the Covid-19 Pandemicmentioning
confidence: 99%
“…Pooled prevalence of anxietyA total of 31 studies reported the prevalence of anxiety during COVID-19 in different samples from South Asian countries[46][47][48][49][50][51][52][53][54][55][56]58,59,[61][62][63][64][65][66]68,69,[71][72][73][74][75][76][77][78][79][80] . These studies used different scales to measureanxiety in respective samples, including the Generalized Anxiety Disorder 7-item (GAD-7) scale (n = 16), Depression, Anxiety and Stress Scale -21 Items (DASS-21) scales (n = 9), Hospital Anxiety and Depression Scale (HADS) (n = 4), Patient Health Questionnaire-4 (PHQ-4) (n = 1), and Self Reporting Questionnaire 20-items (SRQ-20) scale (n = 1).…”
mentioning
confidence: 99%